If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8(c-9)=12c-72-24c
We move all terms to the left:
8(c-9)-(12c-72-24c)=0
We add all the numbers together, and all the variables
8(c-9)-(-12c-72)=0
We multiply parentheses
8c-(-12c-72)-72=0
We get rid of parentheses
8c+12c+72-72=0
We add all the numbers together, and all the variables
20c=0
c=0/20
c=0
| 8=2y+10 | | 13+4x=1-x= | | 4(x+10)=x | | 3a-6=3+6a | | -2(2x+3)=-4(x=1)-2 | | ²x-1/3-6x-2/5=1/3 | | 3(a–5)+19=-2 | | 4x=4x+20 | | 4.6g+2=2.6g+10 | | 3x+15-2x=2x+6 | | 3/3a+2=3/8 | | y–7+4y=13 | | -33=-7x-12-26 | | 30-0,5x=0 | | X+0.6=x+0.1 | | y/9=10/15 | | -8y=16/9 | | |x+3|=6 | | 1/2(x+6)=2x | | 3x+19=119-7x | | 3+19=119-7x | | 3x+20=50-2x | | -28=-4/5y | | T^2+5t=-5t | | 6-12x-20=2 | | 3^x=24 | | 30+8x=6 | | 20x+8x=7 | | 15+(x-5/x)=30 | | 3/8x+5/12=18 | | 5/8+1-7/8x=3/4 | | P^2+35=-12p |